2020
DOI: 10.22270/jddt.v10i2.3920
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Sub-acute Toxic Effects of Algerian Peganum harmala L. Crud Extract

Abstract: The present study was carried out to evaluate the acute and sub-acute toxicity of Algerian Peganum harmala L. seeds (Zygophyllaceae). For the acute toxicity assessment, oral administration of P. harmala crud extract to mice in single doses of 0-12 g/kg caused dose-dependent general behavior adverse effects and mortality with LD50 of 2,86 g/kg. In the sub-acute study, daily oral administration of the crude aqueous extract for 28 consecutive days did not result no mortality. However, our results showed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Then, they were randomly divided into six groups (n = 8): Control (C), diabetic (D), harmine (H), diabetic plus harmine (DH), seed extract (S), and diabetic plus seed extract (DS). A dose of 6.5 mg/kg body weight (BW) of Harmine (Sigma-Aldrich, USA) and 150 mg/kg BW of seed extract was gavaged to the treatment rats for 28 days (24,25).…”
Section: Experimental Designmentioning
confidence: 99%
“…Then, they were randomly divided into six groups (n = 8): Control (C), diabetic (D), harmine (H), diabetic plus harmine (DH), seed extract (S), and diabetic plus seed extract (DS). A dose of 6.5 mg/kg body weight (BW) of Harmine (Sigma-Aldrich, USA) and 150 mg/kg BW of seed extract was gavaged to the treatment rats for 28 days (24,25).…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition, the results of this study are in accordance with previous research findings which revealed that alcoholic extract of harmala seeds at a dose of 3000 mg/kg for 2 weeks caused a significant reduction in body weight in mice (Al-Jborrey and Al-Shahwany, 2017). Rezzagui et al (2020) and Mollashahi and Kazerani (2020) reported that oral administration of methanolic extract of harmala seeds to mice did not cause any significant changes in the body weight. This weight loss might be caused by loss of appetite.…”
Section: Harmala Seeds Extract Exposure Reduced Body Weight But Not L...mentioning
confidence: 99%
“…In parallel with these trials, there have been some studies on adverse effects and safety that are important to review in this section. Among them, an oral administration of P. harmala extract was carried out in mice at a dose of 0–12 g/kg to evaluate the acute toxicity causing adverse effects at an LD 50 of 2.86 g/kg [ 118 ]. In a study to evaluate the subacute effects carried out by the daily oral administration of an aqueous extract for 28 consecutive days, no mortality was obtained, although a significant difference was observed in the weight of the organs between the control animals and those that received the treatment.…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%
“…Only the urinalysis was negative for all parameters except glucose. In addition, from the pathological point of view, some serious abnormalities and histological changes were observed in liver and kidney tissues [ 118 ]. These results give us an idea of the high activity of the alkaloids contained in this plant and therefore of the need to deepen the knowledge of the adverse effects that they could present in humans.…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%